2007
DOI: 10.1088/0953-8984/19/40/406205
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the current–voltage characteristics of Sn/PANI/p-Si/Al heterojunctions

Abstract: Sn/PANI/p-Si/Al heterojunctions were fabricated by electropolymerization of aniline on chemically cleaned p-Si substrates. Current-voltage characteristics of Sn/PANI/p-Si/Al heterojunctions measured in the temperature range 140-280 K are presented and analyzed. Although these devices were clearly rectifying, their I-V characteristics were non-ideal, which can be judged from the nonlinearity in the semi-logarithmic plots. The high values of the ideality factor n depending on the sample temperature may be ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…That is, the shape of the I-V characteristics is not only controlled by the contacts, but strongly depends on the nature of the DNA layer between the Al electrode and the p-Si semiconductor. Generally, double-logarithmic forward bias I-V plots with a slope equal to or larger than 2 suggest the possibility of the SCLC mechanism [50][51][52][53][54]. The double-logarithmic forward bias I-V curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the shape of the I-V characteristics is not only controlled by the contacts, but strongly depends on the nature of the DNA layer between the Al electrode and the p-Si semiconductor. Generally, double-logarithmic forward bias I-V plots with a slope equal to or larger than 2 suggest the possibility of the SCLC mechanism [50][51][52][53][54]. The double-logarithmic forward bias I-V curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traps are locations arising from disorders, dangling bonds, impurities, etc., and are called localized states that very often capture free-charge carriers, playing a very important role in the conduction process of an organic layer [56]. Similarly transport phenomena have been observed in dielectrics, amorphous semiconductors, wide band gap semiconductors, and other organic solids [48][49][50][51][52][53][54][55][56]. It is observed that n is greater than 1 and this is an indication that thermionic emission is not the only operative mechanism for current flow and is usually attributed to a Schottky barrier height which is bias dependent.…”
Section: Resultsmentioning
confidence: 99%
“…The I ‐ V plots follow a power law— I ~ V 4.91 , I ~ V 6.97 , and I ~ V 35.22 . Exponents larger than two suggest there is trap‐charge‐limited conduction with an exponent trap distribution . In the region of higher forward voltage (behind the linear regions), the series resistance plays a decisive role.…”
Section: Resultsmentioning
confidence: 99%
“…Exponents larger than two suggest there is trap-charge-limited conduction with an exponent trap distribution. 32 In the region of higher forward voltage (behind the linear regions), the series resistance plays a decisive role. Figure 3C shows the dark current of the diode in linear coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…As known, the applicability of space-charge limited current (SCLC) mechanism requires, at least, Table 1 Parameters extracted from J-V characteristics of n-Ga0.29 Al0.71As/p-GaAs heterojunction. one Schottky contact at a metal-semiconductor interface (at the junction interface) for continuous supply of injected charge carriers to sustain SCL currents in the material [36,37]. The SCLC conduction should become important when the density of injected free-charge carriers is much larger than the thermal-free-charge-carrier density.…”
Section: Dark Current Density-voltage Properties Of N-algaas/p-gaas Dmentioning
confidence: 99%